STUDY OF THE BIOLOGICAL CHARACTERISTICS OF THE TOMATO PLANT - M.A. Mirzayeva; Mukhtorova Madina Ahmadjon qizi (Web of Journals Publishing, 2025)
This study investigates the main biological characteristics of the tomato (Solanum lycopersicum L.) plant under varying climatic and soil conditions. Key parameters examined include stem and root development, flower and seed formation, and the influence of temperature and soil factors on vegetative growth. Tomato fruits, which are multi-locular and multi-seeded fleshy berries, show wide variation in size and shape: fruit weight ranges from 20–50 g to 500–800 g, with fruits up to 70 g considered small, 70–100 g medium, and over 100 g large. Shapes include flat, round, oval, pear-shaped, and elongated cylindrical forms. The findings contribute to a clearer understanding of how environmental conditions affect tomato morphology and overall plant performance.
Keywords: Climatic conditions, plants, stem, flower, seed, vegetative propagation, seed weight, root system, temperature, soil conditions.